Physical activity and risk of cholelithiasis: a narrative review - Ye, Zhen; Xie, Jinkun; Ni, Xiao; Yang, Jiyong; Li, Jiong; Xuan, Yujun; Gu, Honggang (Frontiers in Medicine, 2024)
Introduction: Cholelithiasis, commonly known as gallstone disease, poses a significant public health concern globally, with a myriad of risk factors contributing to its development. Among these, lifestyle factors, particularly physical activity, have garnered considerable attention for their potential role in modulating the risk of gallstone formation. This review aims to synthesize the current landscape of physical activity and the risk of developing cholelithiasis and identify knowledge gaps. To identify relevant articles, an independent author conducted a literature search using the PubMed database including keywords "cholelithiasis", "gallstones", and "physical activity" with no restriction on publication date. Cohort studies or Mendelian randomization analyses that reported physical activity and risk of gallstone disease were included in the current review. 15 articles were included in this review. The review highlights evidence suggesting a protective effect of regular physical activity against the development of gallstones. Results of Mendelian randomization analyses similarly demonstrated that physical activity remains independently causally associated with cholelithiasis. This review underscores the potential of physical activity as a modifiable risk factor for cholelithiasis, advocating for further research to establish definitive guidelines for prevention through lifestyle modification.